Operating principles and performance of a novel a-Si H p-i-n-based X-ray detector for medical image applications. - Sen-Shyong Fann (IEEE Transactions on electron devices)
This work develops a novel hydrogenated amorphous silicon (a-Si:H) p-i-n photodiode-based X-ray detector aimed at medical image applications. The new detector consists of an a-Si:H p-i-n photodiode and a stacked dielectric layer, deposited on the p-layer (n-i-p-SiNx) or the n-layer (p-i-n-SiNx) of the p-i-n photodiode, as the main charge storage element. This detector operates as a capacitor and is connected in parallel to a reverse-biased p-i-n photodiode during the detection cycle to accumulate photon-converted charges. The junction capacitance (Cj) of the p-i-n diode was enhanced by this stacked dielectric layer without reducing the active area of the detector. The design of the charge storage capacity and the photon-charge transfer efficiency can be optimized separately for various applications. Moreover, the linearity, dynamic range of operation, and data retention capacity of the detector were found to be markedly improved by the enlarged capacitance in the detector. The operating principles and performance of this novel device are discussed, and the corresponding control sequence of the switch of the device array is also addressed. The experimental results proved that this novel structure is valid and can be applied to construct effectively a two-dimensional detection array, offering considerable advantages of the novel device in X-ray medical image applications.